2007
DOI: 10.1111/j.1360-0443.2007.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk behavior among injection drug users in Tehran, Iran

Abstract: This research is one of the first to describe a diversity of IDU, including women and higher socio-economic class individuals, in Tehran. While efforts in harm reduction in Iran to date have been notable, ongoing risks point to an urgent need for targeted, culturally acceptable interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 15 publications
(13 reference statements)
1
71
0
1
Order By: Relevance
“…Other studies have also suggested that the high cost of drug use can contribute to transition to IDU (11,(21)(22)(23), since injecting is the most efficient route. The need to reduce drug expenses is more pronounced in those with scarce economic resources (e.g., homeless and unemployed people) (14,18,24).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also suggested that the high cost of drug use can contribute to transition to IDU (11,(21)(22)(23), since injecting is the most efficient route. The need to reduce drug expenses is more pronounced in those with scarce economic resources (e.g., homeless and unemployed people) (14,18,24).…”
Section: Discussionmentioning
confidence: 99%
“…Although this reflects the fact that the prevalence of injection drug users is considerably lower in women compared with men (1, 5) yet, since women are more likely to accrue harm from drug injection (11,18), epidemiology of ensued complications should be explored more thoroughly for this gender. It is suggested that women are more likely to depend on their partner to help them with injections, hence augmenting the risk of using shared paraphernalia (32,33). In the current study, we only included IDUs admitted to the infectious disease ward and patients admitted elsewhere were not covered.…”
Section: Limitationsmentioning
confidence: 99%
“…Few studies of AIDS-free HIV-infected individuals in Iran have explored the potential impact of factors influencing the time for progression from HIV to AIDS and from AIDS to AIDS-related death. The only information comes from small, unrepresentative samples of the population [1,[10][11][12][13][14][15][16]. Therefore, this retrospective cohort study was designed and conducted in a high middle-income country to estimate the time from the HIV diagnosis to AIDS progression and the time from the AIDS initiation to the AIDS-related death and non-AIDSrelated death.…”
Section: Introductionmentioning
confidence: 99%